Pengaruh Keputusan Investasi dan Keputusan Pendanaan terhadap Nilai Perusahaan pada Sektor Properti, Real Estate, dan Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2013—2017 - Budhi Pamungkas Gautama; Nada Kirana Octavia; Netti Siska Nurhayati (Universitas Winaya Mukti, 2019)
This research is motivated by the decrease of the company value that property, real estate and building construction companies. This research aims to know the description of investment decisions with a measuring indicators that is Total Asset Growth (TAG), description of funding decisions with measuring indicators that is Debt to Equity Ratio (DER) and description company value with a measuring indicator that is Price Book Value (PBV). The analysis tools used include panel data regression analysis, test of significance of regression, and test the significance of regression coefficient. The results showed that the variables Investment decision variable (TAG) does not effect the Corporate Value and Funding Decision (DER) has a positive effect on firm value company values in the property, real estate and building construction sector.